2005
DOI: 10.1152/jn.00200.2004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Contrast on the Active Control of a Moving Line

Abstract: Li, Li, Barbara T. Sweet, and Leland S. Stone. Effect of contrast on the active control of a moving line. J Neurophysiol 93: 2873-2886, 2005. First published December 22, 2004 doi:10.1152/jn.00200.2004. In many passive visual tasks, human perceptual judgments are contrast dependent. To explore whether these contrast dependencies of visual perception also affect closed-loop manual control tasks, we examined visuomotor performance as humans actively controlled a moving luminance-defined line over a range of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 70 publications
4
22
1
Order By: Relevance
“…Figure 7 plots the response gains and phases as a function of input perturbation frequency for the HH and the control groups for both target motion conditions. The decreasing response gain and the steady phase roll-off at high frequencies are consistent with the low-pass gain control with a time delay typically observed in previous active control studies [35], [36], [55].…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Figure 7 plots the response gains and phases as a function of input perturbation frequency for the HH and the control groups for both target motion conditions. The decreasing response gain and the steady phase roll-off at high frequencies are consistent with the low-pass gain control with a time delay typically observed in previous active control studies [35], [36], [55].…”
Section: Resultssupporting
confidence: 88%
“…It has also been shown that human operators can perform such a closed-loop visual motor control task under various controller dynamics [32], [33], [34]. Based on these findings, Li et al have developed a simple closed-loop visual motor control task that involves controlling a randomly moving visual target on the screen to evaluate how the visual system uses different sources of visual information for the control of target motion [35], [36], and how the recruitment of new visual information for visual motor control is affected by controller dynamics [37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the opaque strips used by Gumenik and Glass (1970) reduce words to small visible line segments that may not form an effective Gestalt of a word. By comparison, the effects of contrast which are manifested in early stages of visual processing (Harley, Dillon, & Loftus, 2004;Li, Sweet, & Stone, 2005) appear to slow but not qualitatively alter the outcome of the word recognition process and consequently may not eliminate the Stroop effect.…”
Section: Discussionmentioning
confidence: 86%
“…4. The duration of each trial was 95 s. Following previous studies on manual control (Li et al 2005(Li et al , 2006aLi WO et al 2009), all chosen frequencies for the vehicular heading and orientation perturbations went through an integer number of cycles in 90 s, and we added 5 s in each trial, such that we could skip the initial transient response at the beginning of the trial.…”
Section: Visual Stimuli and Controlmentioning
confidence: 99%